Le développement durable en question(s) - François Mancebo (Cybergeo, 2007)
Development implies structural modifications, whereas sustainability supposes continuity. Which resources have to be preserved for the generations to come, if today we do not know which will be essential? Sustainability makes the dead end on the fact that the history of humanity is an alternation of more or less stationary phases and brutal ruptures. Can we really connect global and local scales in a large machinery, as if same principles governed the whole world and each single place? The truth is, sustainable development dreams of an unrealistic smooth world without clashes, conflicts, crises.